Clinical Studies on Sedative Effect of Butorphanol and Buprenorphine in Bovine - A Rokad, Hardik; H Bhatt, Raghuvir; H Sharma, Avanee; D Dodia, Vaibhav; V Vadalia, Jignesh; R Padaliya, Nilesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present clinical study was conducted on 24 bovines scheduled for major surgical procedures. The animals were randomly divided  into four groups (n=6 each) to evaluate the preanaesthetic effect of Butorphanol and Buprenorphine. Animals in groups I and II, were  premedicated with Butorphanol (0.02 mg/kg, IV), while in groups III and IV, Buprenorphine (0.006 mg/kg, IV) was used. Induction  agent used in all 4 groups was a mixture of Ketamine HCl (1 gm) and Guaifenesin (25 gm) diluted in 500 mL of 5% dextrose and given  intravenously “till effect”. All animals were orotracheally intubated after induction of anaesthesia. In group I and III, Isoflurane and 100  % oxygen mixture was used as per demand of the cases, while a double drip of Ketamine and Guaifenesin mixture was given in groups  II and IV to achieve the desired depth of surgical anaesthesia throughout the period of surgery. Evaluation of anaesthetic efficacy was  made by determining the dose of induction agent (total dose), duration of maintenance anaesthesia (min), duration of surgery (min)  and recovery time (min). A combination of Butorphanol and Buprenorphine provided good to excellent quality of sedation as compared  to Butorphanol alone in bovine. Buprenorphine showed potent dose sparing effect on induction and maintenance dose of Ketamine  and Guaifenesin or Isoflurane than Butorphanol in bovine.
Keywords: Bovine; Buprenorphine; Butorphanol; Guaifenesin; Isoflurane; Ketamine